Mitigasi Risiko pada Proses Produksi Tahu Menggunakan Pendekatan Metode Failure Mode and Effect Analysis dan Risk Priority Number - Arsyad Sumantika; Bahariandi Aji Prasetyo; Ganda Sirait (SURYA TEKNIKA, 2024)
The Bantul Tofu Industry is a medium-sized industry that processes soybeans into tofu located in the Bantul area. In the production process there are still errors that cause the tofu product to be damaged. The aim of this research is identify risks that occur in tofu production, analyze priority risk events, and make recommendations for improvements. The method used is FMEA to analyze the occurrence of risks or failures in a process and RPN to provide a risk assessment score for proposed improvements. Based on the research results, it was found that there were 14 total risk events and there were 5 risks that were mitigation priorities, such as spilling of tofu coconut milk, mixing of soybean quality, incorrect cutting of tofu, slippery production floors, and the presence of liquid waste. Recommendations for improvement are creating SOP, using adequate equipment, maintaining the cleanliness of production areas and routine maintenance. Keywords: Failure Mode and Effect Analysis, Risk Priority Number, Tofu Processing